KINERJA PEMERINTAH KECAMATAN DALAM PELAYANAN KARTU TANDA PENDUDUK (e-KTP). (Suatu Studi Di Kantor Kecamatan Passi Barat Kab. Bolaang Mongondow) - Ime, Sefti Sari; Rompas, Welson Yapi; Rares, Joyce Jecinta (JURNAL ADMINISTRASI PUBLIK, 2014)
Embodiment and real commitment from government service provided is in the form of performance. In Reinventing Governmentmovement, performance is no longer me asured by how much input and how the procedures in the journey to achieve an output as the commonly held, but with emphasis on the end result that really-really felt the customer sort he public (Osborne &Geabler, 1993;Barzesley, 1992; Osborne&Plastrik, 1997). The Assertion is based on the fact that the government's accountability to the public during this time, which is manifested in the form of Performance is still very minimal. One of the problems in the public service are often people complain about the service in the manufacture of Electronic Identity Card(e-KTP), the e-KTP program is program launched by the Ministryof Internal Affairsof the Republic of Indonesiain February 2011. And that is examined in this case is District Government performance of services Identity Card(e-KTP) as a service provider inWestern Passisub-District Office. Research Methodology: This study use da descriptive qualitative research methods throughin-depth interviews to15 informants, observation, and tracking of documents in aid with additionalin strumentssuch as interview guides, tape recorders, and stationery. Results:Based on performance indicators Productivity, Quality of Service, Responsiveness, Responsibility, and Accountability, it is known that the performance of the District Government in the creation of e-KTP service is quite good although there are still some problems such as the destruction ofrecording equipment service activities that cause the creation of e-KTP inhibited. Conclusion: The performance of the sub-District Government of west Passian e-KTPÂ  card service based on research at the west Passi sub-District Office can be said is good enough. Keywords: Performance of the DistrictGovernment, ServiceIdentity Card